Concurrent working memory task increases or decreases the flanker-related N2 amplitude - Wei, Hua; Yao, Yuan; Zhou, Lili (Frontiers in Psychology, 2022)
Concurrent working memory (WM) task reduces available attentional control resources to perform the flanker task. However, controversy exists as to whether concurrent WM task increases or decreases flanker-related N2 amplitude. In a flanker task experiment, individuals were confronted with a low, middle, or high WM load task, while electroencephalography (EEG) data were recorded. The ERP results showed a larger flanker-related N2 amplitude while completing a middle or high WM load task compared to a low one. However, completing an additional high WM load task could not increase flanker-related N2 amplitude versus completing an additional middle WM load task. In sum, these results suggest that WM load can impair top-down cognitive control processes, thereby hampering flanker task performance. Importantly, the present study supports the account of flanker-related N2 processes linked to top-down attentional control resource allocation, but challenges the account of flanker-related N2 reflecting response conflict processes.